Agathokles / von Caroline Pichler, gebornen von Greiner. - Pichler, Caroline, 1769-1843. (Tufts University. Tisch Library., 2015)
Volume 2 of 3.; Neue, verbesserte Aufl.; 1 online resource (3 volumes); Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.